Virtual Power Plant Solution for Future Smart Energy Communities (Taylor & Francis, 2023)
This book provides a general overview of virtual power plants (VPP) as a key technology in future energy communities and active distribution and transmission networks for managing distributed energy resources, providing local and global services, and facilitating market participation of small-scale managing distributed energy resources and prosumers. The book also aims at describing some practical solutions, business models, and novel architectures for the implementation of VPPs in the real world. Each chapter of the book begins with the fundamental structure of the problem required for a rudimentary understanding of the methods described. It provides a clear picture for practical implementation of VPP through novel technologies such as blockchain, digital twin, and distributed ledger technology. The book will help the electrical and power engineers, undergraduate, graduate students, research scholars, and utility engineers to understand the emerging solutions regarding the VPP concept lucidly.
English
Keywords: thema EDItEUR::T Technology, Engineering, Agriculture, Industrial processes::TH Energy technology and engineering::THR Electrical engineering; thema EDItEUR::T Technology, Engineering, Agriculture, Industrial processes::TH Energy technology and engineering::THY Energy, power generation, distribution and storage; thema EDItEUR::T Technology, Engineering, Agriculture, Industrial processes::TJ Electronics and communications engineering::TJF Electronics engineering; Virtual,Power Plant, Future Smart Energy Communities